Designer Babies are No Longer Science Fiction: What are The Ethical Considerations? - Khairatun Hisan, Urfa; Romero, Cyril B. (Bincang Sains dan Teknologi, 2023)
Designer babies, a concept once relegated to science fiction, are now a burgeoning topic of discussion and exploration in genetics and bioethics. This paper provides a comprehensive overview of the designer baby phenomenon, examining its definition and evolution from cinematic fantasy to scientific possibility. We delve into the intricate mechanisms behind designer babies, shedding light on the genetic engineering technologies, particularly CRISPR, that underpin this concept. While these technologies hold immense promise, they are still nascent, awaiting rigorous development and ethical scrutiny. The paper highlights the current state of designer baby research, emphasising that successful implementations on human subjects remained unverified as of its writing. Notably, we recount the controversial case of He Jiankui, whose unapproved and ethically questionable experimentation with CRISPR on embryos in China sent shockwaves through the scientific community. The arguments surrounding designer babies are dissected, presenting both proponents' views, such as the potential to eradicate genetic diseases and enhance human potential, and critics' concerns about ethical dilemmas, reduced genetic diversity, social inequality, and unpredictable consequences. Ethical considerations are paramount, touching upon human dignity, social justice, eugenics, unintended consequences, autonomy, and the impact on religious and moral convictions. Once a fantastical notion, designer babies have become a tangible subject of scientific inquiry and ethical discourse. This paper endeavours to provide a comprehensive understanding of the multifaceted dimensions surrounding designer babies, allowing readers to contemplate the ethical, social, and scientific implications of a future where genetic engineering may shape the very essence of human existence. As society grapples with these profound questions, we must navigate this uncharted territory with wisdom, responsibility, and an unwavering commitment to ethical principles.